CLICKING UNDER PRESSURE: A NETNOGRAPHIC INVESTIGATION OF FOMO AND IMPULSIVE BUYING IN FLASH SALE CAMPAIGNS - Gautama Sastra Waskita; Sawal Sartono; Desi Rachmawati (BEMJ: Business, Entrepreneurship, and Management Journal, 2025)
Flash sale campaigns have become a dominant digital marketing tactic, yet their heightened temporal pressure often triggers consumers’ fear of missing out (FOMO), leading to unplanned and impulsive purchases. However, empirical understanding of how these psychological dynamics unfold within real consumer communities remains limited. This study aims to explore how FOMO is constructed, expressed, and translated into impulsive buying behavior during flash sale events. Employing a netnographic methodology, data were collected from online consumer forums and social media discussions to capture naturally occurring narratives and behavioral cues. The findings reveal three main patterns: collective emotional contagion that amplifies FOMO, heuristic-driven decision-making under time pressure, and social validation loops that normalize impulsive buying. These insights deepen theoretical understanding of digital consumer psychology and provide actionable implications for ethical marketing practices, particularly in managing persuasive design within flash sale environments.